Penerapan Konsep Student - Centered Learning dalam Pendidikan Tinggi Studi Kasus pada Bidang Studi Akuntansi - Elisabeth Cintya Santosa (Jurnal Akuntansi, 2007)
Business environment nowdays gives a tough challenge for education world. They asks education system to promote component human resource for the employee market. Thosechallenges make the universities to prepare themselves in order to improve the quality of their education system. therefore, it is needed more effective teaching and learning in the process of improving the quality of education. This paper tries to give comprehension from TCCO concept to SCL concept which is a new breaktrough learningfor students. This learning focuses on “learning process” for studentor named it as student centered learning - SCL. SCL means that learning tries to make students to be grown up in their thinking, skills and attitudes. therefore, the role of teacher in this method is as a facilitator or a motivator. This concept will is better to be implemented for introduction accounting cource.Keywords : Student-Centered Learning (SCL), T eacher-Centered Learning ( TCL)